Predicting stochastic harmonics of multiple converters in a power system (microgrid) - Ivry, Preye Milton (2016)
The microgrid concept integrates Renewable Energy Systems (RES) to the Electrical Power System (EPS) as a means to produce clean energy, meet consumer energy demands and preserve the depleting fossil fuels reserves. These RES are usually interfaced to the grid using power electronic converters (such as Voltage Source Converters) to achieve the required control and conversion of power. Nevertheless, Voltage Source Converters (VSCs) produce both current and voltage harmonics which negatively impact on the Power Quality (PQ) of a microgrid and may cause damage or malfunctions of equipment.